Is there any association between early trimester Triglyceride–glucose index and incidence of hypertensive disorder of pregnancy and adverse pregnancy outcomes? - Yali Pan; Su Zou; Yingjia Xu; Ruomin Di; Huafen Gu; Zhangsheng Wang; Xiang Wei; Chenxi Yang; Gaofeng Zhang (Frontiers in Endocrinology, 2023)
BackgroundInsulin resistance (IR) is a normal feature of pregnancy and plays a crucial role in the pathophysiology of hypertensive disorder of pregnancy (HDP). The triglyceride-glucose index (TyG index) has been shown as a simple and reliable alternative IR marker. This work aimed to investigate the association between the TyG index and the incidence of HDP and adverse pregnancy outcomes.MethodsFrom January 2016 to December 2018, 289 women with HDP and 861 women without HDP were recruited at Shanghai Fifth People’s Hospital, Fudan University to determine the relationship between the TyG index and the incidence of HDP and adverse pregnancy outcomes.ResultsIn the case-control study, the incidence of HDP was found to be significantly associated with the TyG index. Moreover, logistic regression indicated that the TyG index is an independent risk factor for HDP development and incidence of low birth weight (LBW) and fetal distress. In the cohort study, the results showed that the TyG index increased, there was a stepwise increase in HDP incidence, SBP, and DBP levels one week before delivery as well as in LBW and fetal distress incidence. The early trimester TyG index was positively associated with pre-pregnancy BMI, systolic blood pressure (SBP), and diastolic blood pressure (DBP) one week before delivery. Spline regression showed that there was a significant linear association between HDP incidence and early trimester TyG index when it was >8.5.ConclusionsThis work suggested that the early trimester TyG index was closely associated with the development of HDP and adverse pregnancy outcomes.